Determinantes da eficiência econômica do setor elétrico : um estudo de empresas da Península Ibérica e Brasil - Rech, Mariliza (Universidade do Vale do Rio dos Sinos, 2017)
Electricity, as a non-storable product which varies in short periods of time, is essential for the functioning of society and has its price as a decisive factor for competitiveness. On the other hand, the correct management of costs allows obtaining a superior profitability. An alternative to determine the magnitude of costs is to measure the efficiency of operations. Therefore, the best results achieved are directly related to the better economic efficiency achieved by energy companies, and thus the characteristics that make a company more efficient represent important elements to be identified. Considering the contribution that the relative efficiency of companies under international standards may add to the development of the sector, this cross-country research analyzes the determinants of the relative economic efficiency of public companies in the Brazilian electric sector and the Iberian Peninsula.. It is a descriptive study, with a quantitative approach, carried out with data from the period of 2010 to 2014. Using econometric methods, the relative economic efficiency of 38 companies of the population was determined, which resulted in 190 observations. As a result of the study, it was identified that the fact of belonging to the Iberian Peninsula represents a positive impact on the Ebitda, generating higher results in relation to the Brazilian sample. The company Cemig - GT stood out among the Brazilian companies. Regarding the analyzed variables, per capita consumption (GWh), fixed assets and number of employees were identified as explanatory factors to obtain efficiency. It was concluded that the companies with the highest economic efficiency obtained through the more efficient use of their fixed assets and employees resources, as well as reductions in per capita consumption and Ebitda increases.
Keywords: Eficiência econômica; Setor elétrico; Península Ibérica; Economic efficiency; Electrical sector; Iberian peninsula; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis